Integrative transcriptome and microRNome analysis identifies dysregulated pathways in human Sertoli cells exposed to TCDD - Ribeiro, Mariana A. [UNESP]; Estill, Molly S.; Fernandez, Geysson J. [UNESP]; Moraes, Leonardo N. [UNESP]; Krawetz, Stephen A.; Scarano, Wellerson R. [UNESP] (Elsevier, 2018)
Male fertility and spermatogenesis are directly linked to the Sertoli cell's ability to produce factors associated with germ cell development. Sertoli cells express receptors for FSH and testosterone, and are the major regulators of spermatogenesis. Recent studies report that regulatory RNA molecules, such as microRNAs (miRNAs), are able to modulate testicular function during spermatogenesis and that their altered expression may be involved in male infertility. miRNAs may play a role in the response to xenobiotics that have an adverse consequences to health. An important group of xenobiotic organic compounds with toxic potential are dioxins, such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Experimental models of TCDD exposure in mice demonstrated that TCDD exposure causes low sperm count and delayed puberty. This study below examines the mechanism of TCDD's action in human Sertoli cells, through interrogating the expression profile of miRNAs and mRNAs, that enabled us to identify dysregulated molecular pathawys in Sertoli cell. 78 miRNAs presented altered expression, with positive regulation of 73 and negative regulation of 5 miRNAs when compared to the control group. Regarding gene expression profile, 51 genes were deregulated, of which 46 had positive regulation and 5 genes with negative regulation. Important pathways have been altered by the action of TCDD as AhR pathway, GPR68, FGF2 and LIF. This study has opened the door to new perspectives on the TCDD toxicity pathway as it affects Sertoli cells physiology that can ultimately lead to male infertility.
Keywords: Infertility; miRNA; RNAseq; Sertoli cell; TCDD